Magnetorotational instability in cool cores of galaxy clusters. (October 2015) - Nipoti, Carlo; Posti, L.; Ettori, S.; Bianconi, M.
Abstract : Clusters of galaxies are embedded in halos of optically thin, gravitationally stratified, weakly magnetized plasma at the system's virial temperature. Owing to radiative cooling and anisotropic heat conduction, such intracluster medium (ICM) is subject to local instabilities, which are combinations of the thermal, magnetothermal and heat-flux-driven buoyancy instabilities. If the ICM rotates significantly, its stability properties are substantially modified and, in particular, also the magnetorotational instability (MRI) can play an important role. We study simple models of rotating cool-core clusters and we demonstrate that the MRI can be the dominant instability over significant portions of the clusters, with possible implications for the dynamics and evolution of the cool cores. Our results give further motivation for measuring the rotation of the ICM with future X-ray missions such as ASTRO-H and ATHENA.